2021
DOI: 10.1002/1873-3468.14174
|View full text |Cite
|
Sign up to set email alerts
|

An updated classification and mechanistic insights into ligand binding of the substrate‐binding proteins

Abstract: Substrate‐binding proteins (SBPs) mediate ligand translocation and have been classified into seven clusters (A‐G). Although the substrate specificities of these clusters are known to some extent, their ligand‐binding mechanism(s) remain(s) incompletely understood. In this study, the list of SBPs belonging to different clusters was updated (764 SBPs) compared to the previously reported study (504 SBPs). Furthermore, a new cluster referred to as cluster H was identified. Results reveal that SBPs follow different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Three‐dimensional structure prediction revealed that the structure of the protein SerBP (Figure 4b) was highly similar to that of the LAO (Figure 4c) and HisJ (Figure 4d), with RMSD being 0.630 and 0.784 Å, respectively. Both of the LAO and HisJ SBPs belonged to class F of ABC transporter [26]. This kind of SBP consists of two domains connected by two hinge regions of about 8–10 amino acids residues, with the ligand‐binding site buried in the gap between the two domains, and the ligand of this class F SBPs is usually amino acids [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional structure prediction revealed that the structure of the protein SerBP (Figure 4b) was highly similar to that of the LAO (Figure 4c) and HisJ (Figure 4d), with RMSD being 0.630 and 0.784 Å, respectively. Both of the LAO and HisJ SBPs belonged to class F of ABC transporter [26]. This kind of SBP consists of two domains connected by two hinge regions of about 8–10 amino acids residues, with the ligand‐binding site buried in the gap between the two domains, and the ligand of this class F SBPs is usually amino acids [26].…”
Section: Resultsmentioning
confidence: 99%
“…Both of the LAO and HisJ SBPs belonged to class F of ABC transporter [26]. This kind of SBP consists of two domains connected by two hinge regions of about 8–10 amino acids residues, with the ligand‐binding site buried in the gap between the two domains, and the ligand of this class F SBPs is usually amino acids [26]. Therefore, we speculated that the protein encoded by the mutant gene might be an orphan SBP of the ABC transporter to transport a certain amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…One group of proteins that have been used for this purpose are periplasmic binding proteins (PBPs). They are involved in the cellular transport of a wide variety of small molecules such as carbohydrates, amino acids, vitamins and ions (Chandravanshi et al, 2021;Felder et al, 1999). The structurally symmetric bilobal architecture of their fold has long been thought to originate from a duplication and fusion event of an individual lobe (Fukami-Kobayashi et al, 1999;Louie, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…ABC transporters typically consist of a substrate binding protein (SBP), one or two hydrophobic membrane-spanning permeases, and one or two nucleotide-binding ATPases that supply the energy for active transport of the metal ion. SBPs are lipoproteins that localize to the membrane via the secretory (Sec) pathway in Gram-positive bacteria and are further organized into eight clusters, named A–H, based on protein structure and the binding dynamics that are outlined in Table 1 [ 8 , 9 , 10 ]. Typically, metal binds at the cleft between two conserved domains that are connected by an α-helical linker, which closes in most SBPs to bury the metal ion.…”
Section: Introductionmentioning
confidence: 99%